Unlocking longevity: the role of telomeres and its targeting interventions - Schellnegger, Marlies; Hofmann, Elisabeth; Carnieletto, Martina; Kamolz, Lars-Peter (Frontiers in Aging, 2024)
Average life expectancy has been steadily increasing in developed countries worldwide. These demographic changes are associated with an ever-growing social and economic strain to healthcare systems as well as society. The aging process typically manifests as a decline in physiological and cognitive functions, accompanied by a rise in chronic diseases. Consequently, strategies that both mitigate age-related diseases and promote healthy aging are urgently needed. Telomere attrition, characterized by the shortening of telomeres with each cell division, paradoxically serves as both a protective mechanism and a contributor to tissue degeneration and age-related ailments. Based on the essential role of telomere biology in aging, research efforts aim to develop approaches designed to counteract telomere attrition, aiming to delay or reduce age-related diseases. In this review, telomere biology and its role in aging and age-related diseases is summarized along with recent approaches to interfere with telomere shortening aiming at well- and healthy-aging as well as longevity. As aging research enters a new era, this review emphasizes telomere-targeting therapeutics, including telomerase activators and tankyrase inhibitors, while also exploring the effects of antioxidative and anti-inflammatory agents, along with indirectly related approaches like statins.